Identifying the occurrence of lightning and transient luminous events by nadir spectrophotometric observation. (July 2016) - Adachi, Toru; Sato, Mitsuteru; Ushio, Tomoo; Yamazaki, Atsushi; Suzuki, Makoto; Kikuchi, Masayuki; Takahashi, Yukihiro; Inan, Umran S.; Linscott, Ivan; Hobara, Yasuhide; Frey, Harald U.; Mende, Stephen B.; et al.
Abstract: We propose a new technique to identify the occurrence of lightning and transient luminous events (TLEs) using multicolor photometric data obtained by space borne nadir measurements. We estimate the spectral characteristics of lightning and TLEs by converting the optical data obtained by the ISUAL limb experiment to the GLIMS nadir geometry. We find that the estimated spectral shapes of TLE-accompanied lightning are clearly different from those of pure lightning. The obtained results show that (1) the intensity of FUV signals and (2) the ratio of 337/red (609–753 nm) spectral irradiance are useful to identify the occurrence of TLEs. The occurrence probabilities of TLEs are 10%, 40%, 80%, in the case of lightning events having the 337/red spectral irradiance ratio of 0.95, 2.95, 14.79, respectively. By using the 60% criterion of the 337/red ratio and the existence of FUV emissions, we classify the 1039 GLIMS-observed lightning events into 828 pure lightning and 211 TLE-accompanied lightning. Since the GLIMS trigger level is adjusted to observe extremely-bright events, the occurrence probability of TLEs obtained here most probably reflects the characteristics of energetic lightning. The estimated global map is consistent with previously determined distributions: the highest activities of lightning and TLEs are found over the North/South American continents, African continent, and Asian maritime regions. While the absolute occurrence number of pure lightning and TLE-accompanied lightning are found to maximize in the equatorial region, the occurrence probability of TLEs possibly increase somewhat in the mid-latitude region. Since the occurrence probabilities of TLEs are higher over the ocean than over land, it is likely that the GLIMS-observed TLEs are due primarily to elves which tends to occur more frequently over the ocean. Highlights: A new method to identify the occurrence of lightning and TLEs from satellite nadir measurements is proposed. The method utilizes the FUV emission intensity and the 337 nm to broadband red intensity ratio observed by spectrophotometer. The global map obtained from the proposed method is consistent with previously determined distributions.